The last Elvis [videorecording (DVD)] - Bo, Armando; McInerny, John; Siciliani, Griselda, 1978-; Lopez, Margarita (Actor) ([Publisher not identified], 2014)
Most evenings in Buenos Aires, 'Elvis' Gutiérrez is a star, his singing and stage presence bring back to life the King of Rock and Roll in all his glory. By day, though, Gutiérrez slaves away at a dead-end factory job and endures the scorn of his ex-wife. Only his young daughter, Lisa Marie, brings any joy outside of his Elvis tribute gigs. Feeling more connected to his stage persona than to the world around him, Gutiérrez retreats from reality until a tragic accident.